Effects of Artemisia annua supplementation on the performance and gut health of laying hens challenged with mixed Eimeria species - Sharma, Milan Kumar; Liu, Guanchen; Choppa, Venkata Sesha Reddy; Rafieian-Naeini, Hamid Reza; Mahdavi, Fatemeh Sadat; Marshall, Brett; Gogal, Robert M.; Kim, Woo Kyun (Frontiers in Physiology, 2024)
Background Coccidiosis outbreaks in susceptible laying hens can significantly decrease egg production and cause substantial economic loss to the egg industry. The supplementation of poultry diets with chemotherapeutic agents is limited due to antimicrobial resistance and residue in poultry meat or processed products. Therefore, alternative strategies to control coccidiosis are needed, and Artemisia annua (AA) might have the potential to be a phytogenic feed additive, an alternative to anticoccidial agents. This study aimed to investigate the effect of the dietary supplementation of powdered AA on the performance and gut health of laying hens infected with coccidiosis by Eimeria spp. Methods A total of 225 Hy-Line W-36 laying hens at 23 weeks of age were allocated into 5 treatment groups: 1) control (NC), 2) pair-fed (PF) control, 3) challenged control (CC), 4) CC with dietary inclusion of 0.5% AA (0.5AA), and v) CC with dietary inclusion of 1% AA (1AA). The hens in the CC, 0.5AA, and 1AA groups were orally inoculated with sporulated oocysts of Eimeria maxima (12,500), Eimeria tenella (12,500), and Eimeria acervulina (62,500) at week 25. The PF hens received the same amount of feed consumed by the CC hens from 0–14 days post-inoculation (dpi) of Eimeria spp. The performance of the laying hens, including body weight (BW), hen–day egg production (HDEP), feed intake (FI), and feed conversion ratio (FCR), was measured weekly. Additionally, markers of intestinal health, including gut permeability, lesion score, intestinal morphometry, and immune responses, were evaluated at 6, 14, and 21 dpi. Results At 6 and 14 dpi, laying hens challenged with Eimeria spp. had a lower BW than PF and NC hens (p < 0.0001). Supplementation of 1% AA improved the HDEP by 8.1% compared to CC hens; however, it was still 15.4% lower than that of PF hens (p < 0.0001). The inclusion of 1% AA did not have any beneficial effect on FI; however, the FCR was improved by 0.61 (2.46) than that of CC hens (3.07; p < 0.0001). The inclusion of 1% AA reduced the severity of the intestinal lesions and increased the recovery of intestinal villi (p < 0.05). Additionally, gut permeability was significantly different between the challenged and non-challenged hens; however, among the challenged hens, the inclusion of AA reduced the gut permeability by 29% compared to CC hens (p < 0.0001). Furthermore, the inclusion of 0.5% AA reduced the inflammatory responses in the infected hens. Conclusion Dietary inclusion of AA partially restored the performance and gut health of the laying hens and modulated their inflammatory immune response following Eimeria infection; however, further studies are needed to better understand the mode of action and effective dosages to improve the gut health without negative impacts on the performance.